Human microbiome and environmental disease - Gary Zhang; Henry H Heng (Wolters Kluwer Medknow Publications, 2017)
The importance of human microbiota and their genomes, human microbiome, in health and disease has been increasingly recognized. Human microbiome has tremendous impact in our pathophysiology by modulating metabolic functions, protecting against pathogens, and educating the immune system. In particular, human microbiome is a major player at the interface between humans and their environment and therefore is crucial to the development of environmental disease. In this article, we briefly summarize and interpret the recent advances in the understanding of the roles of human microbiome in environment-related health and disease, and call for a more systematic integration of human microbiome and environmental disease research within the framework of evolutionary medicine.